Integrated modeling to identify priority areas for the conservation of the endangered plant species in headwater areas of Asia. (October 2019) - Han, Yuhui; Dong, Shikui; Wu, Xiaoyu; Liu, Shiliang; Su, Xukun; Zhang, Yong; Zhao, Haidi; Zhang, Xiaolei; Swift, David
Highlights: Endangered plants in Sanjiangyuan mainly locate in the east and the south. Distribution of endangered plants will expand to the west and north in the future. Habitats in the northeast are at the highest ecosystem risk. Most of the highest risk areas are not strictly protected. Abstract: Sanjiangyuan, called the "Water tower of Asia", is critically important in the ecological services of water provision and regulation and in biodiversity conservation. To strengthen protection in this eco-region, The Chinese government established the Sanjiangyuan National Nature Reserve (SNNR) in 2001 and Sanjiangyuan National Park (SNP) in 2014. To assess the effectiveness of these two conservation practices, on the endangered plant species, we used an integrated method to identify the priority areas of the endangered plant species in the Sanjiangyuan Area which showed if some areas need more conservation efforts. After identifying the potential habitats of high-valued species in Sanjiangyuan with MaxENT, a model that combined the hotspots of endangered plant species richness (H), vegetation condition (V), soil condition (S), human disturbance (D) and climate change impact (C) was used to calculate ecosystem risk (ER) associated with each habitat. Projections of climate modeling show that the distribution of endangered plants in Sangjiangyuan will expand to the west and north with the warmer and wetter climate in the future. In both current and future scenarios, the habitats in the northeast of the SNNR are at the highest ecosystem risk and need to be protected strictly. However, most of the high ecosystem risk/conservation priority regions we identified - either current or predicted future status (in 2070 under RCP 2.6) were not protected by SNNR or SNP. Identified conservation gaps call for the well-targeted planning and delineated scientific interventions for protecting the key habitats of these endangered plant species. Conservation priority should be given to eastern Xinghai County and northeastern Tongde County in the east of SNNR, where the habitats are at high ecosystem risk and have high conservation priority.